Methodology Of Tehran University Of Medical Sciences Articles Indexed In PubMed: 2012 - Mohammad Reza Alibeik; Zeinab Bagheri; Niloofar Mohaghegh; Hamid Haghani (Tehran University of Medical Sciences, 2015)
Background and Aim: Materials and methods, as one of the most important parts of a paper, introduces its scientific value. This study aims to investigate the methodological quality of publications of Tehran University of Medical Sciences (TUMS) indexed in PubMed. Materials and Methods: In this descriptive, cross-sectional study, 400 articles affiliated to Tehran University of Medical Sciences and indexed in PubMed until the end of 2012 were investigated. The type, purpose and subject matter of all these articles were recorded in a checklist.  Results: The most frequently published reports were cross-sectional studies (41.3%), followed by case-control studies (14.5%), case reports (14.3%), clinical trials (13%), narrative reviews (4.8%), animal studies (3.3%), quantitative studies (2.8%), quasi-experimental studies (2%), cohort studies (1.8%), case series (1%), meta-analysis (1%), and systematic reviews (0.5%). When the articles were classified according to National Library of Medicine (NLM) classification, most papers were about musculoskeletal system (8.5%). Over half of the articles were therapeutic (52.8%), followed by diagnostic (24.8%), prevention (12.3%), prognostic (7.8%), and etiologic (2.5%). School of Medicine, Hazrate Rasoule Akram hospital, and Endocrinology & Metabolism Research Institutes had the highest number of articles among TUMS faculties, hospitals, and research centers. Conclusion: Primary studies were the most common types observed in the articles affiliated to Tehran University of Medical Sciences. Systematic reviews and meta-analyses form only a small proportion of articles in the current research. It seems that there should be a revision in the researchers' priorities to publish papers with prevention purposes.